Answer:
B. x^3 + 3x^2
Step-by-step explanation:
Volume of a rectangular prism=width * length * height
V=w*l*h
h=3 greater than the length of the base
h=x+3
Length of the base=x
Width=x
Substituting values into the formula
V=w*l*h
=(x)*(x)*(x+3)
Multiplying
=(x^2)(x+3)
=x^3 + 3x^2
Option B is the correct answer
Answer:
Step-by-step explanation:
3b⁵ + 15b⁴ - 18b⁷ = 3b⁵ + [3*5*b⁴] - [6*3*b⁷]
=3b⁴*( b + 5 - 6b³)
Answer:
7 hundredths
Step-by-step explanation:
add 4 to 6 and take away 3
Answer:
2, 4, 5
Step-by-step explanation:
Answer:
√2 + x
Step-by-step explanation:
To obtain the hypotenus, h:
Using Pythagoras rule :
h² = opposite² + Adjacent²
Opposite = √2
Adjacent= x
h² = (√2)² + x²
Take the square root of both sides
h = √2 + x
Hence, the hypotenus is √2 + x